The Evidence Base for Interventions Targeting Individuals With Work-Related PTSD: A Systematic Review and Recommendations. Issue 2 (March 2018) - Torchalla, Iris; Strehlau, Verena
The purpose of this study was to summarize the evidence base for interventions targeting individuals with work-related posttraumatic stress disorder (PTSD), to make recommendations for clinicians and administrative decision makers involved in their rehabilitation, and to guide future research in this area. Particular attention was given to studies that were conducted in naturalistic clinical settings or in a workers' compensation claim context. Electronic searches of Cochrane Central Register of Controlled Trials, MEDLINE, PubMed, PsycINFO, CINAHL, PILOTS, and EMBASE identified 11 articles. Study populations included railroad personnel, police officers, disaster workers, and individuals with industrial injuries. Interventions included trauma-focused cognitive-behavioral therapy and eye movement desensitization and reprocessing. Several studies specifically targeted workers who had failed to return to work (RTW) after standard PTSD treatment. The results suggest that psychotherapy interventions are beneficial for helping clients recover from PTSD symptoms and RTW. In studies that reported on work status, RTW rates increased over time and generally lay between 58% and 80% across follow-up time points. Narrative impressions were supplemented by calculation of Risk Differences for individuals working at pretreatment versus posttreatment. Clinical consideration, methodological issues limiting the current body of work, and recommendations for future research are discussed.